A cross-multilayer mechanism design for improving video quality of SVC coded video streams over mobile WiMAX networks. (1st January 2011) - Tu, Jiun-Yu; Wu, Jung-Shyr; Hsu, Chiung-Fang
Toward the next generation network (NGN), various mobile devices provide users with abilities of ubiquitous computing and communications, however, with different quality of service (QoS) requirements at the same time. With limited wireless network resource, efficient data transmission is critical to meet different QoS requirements. Scalable video coding (SVC) is expected as an appropriate technology to achieve diverse QoS requirements of multimedia video services in the NGN network. In this paper, we expose a challenge when transmitting SVC video streams over existing open-system-interconnection-based networks. We propose a solution to the challenge and degrade video quality corruption when network resource is stringent. While transmitting SVC streams over QoS enabled mobile worldwide interoperability for microwave access (WiMAX) networks, our proposed cross-multilayer mechanism enables classification and prioritisation of SVC video data according to the significance for decoding dependency. In addition, by completely compatible with mobile WiMAX, our mechanism is easily deployable. Simulations validate performance improvement of our mechanism.